REDUCTION IN THE MOVIE SUBTITLE ENTITLED THE BOSS BABY - Gretty Yan Ari Dewi; Dwi Aji Prajoko (Universitas Katolik Widya Mandala Surabaya, 2022)
Translation had become a part of our lives, especially in the movie industry. Translation was needed by those needing any help understanding the meaning. In translating language units such as words, phrases, and clauses, the translation techniques were needed. The assumption that subtitling needs space saving made reduction translation techniques were badly required. Reduction consisted of two types of translation techniques, namely concision and deletion. This research aimed to find language units from The Boss Baby movie subtitle translated with concision and deletion translation technique. This study was descriptive qualitative research. The data collection technique was document analysis. The data analysis technique was etnographic, namely by differentiating the data with non-data, taxonomizing the data, describing their components, and analyzing their cultural theme. The findings showed that language units that was translated with concision translation techniques are 35 data and deletion 23 data. The most dominant was concision. Myriad data about reduction conformed significantly the previous researches by Fitria (2015) about subtitling and Fitria (2018) about the translation of journal. Nevertheless, the findings did not conform the reduction in Prafitasari, et al., (2019) doing research on the poem translation.